Empirical evidence on circular economy and economic development in Europe: a panel approach - Georgescu, Irina; Kinnunen, Jani; Androniceanu, Ane-Mari (Journal of Business Economics and Management, 2022)
Sustainable economic growth is desired to be achieved by governments targeting economic, social, and environmental benefits. The idea of circular economy model is to consider feedback effects from proper waste management instead of one-way effects typical with the classical linear model. Several sectors of society contribute to circular economy and its monetary and environmental outputs in a sustainable way. The aim of this paper is to analyze the dependencies and causalities of circular economy and economic developments in the EU. The research objectives include testing (i) whether research and development (R&D) expenditure, GDP per capita and generation of municipal waste per capita influence the recycling rate of municipal waste, and (ii) whether R&D expenditure, generation of municipal waste per capita and the recycling rate of municipal waste influence the GDP per capita. The relevant indicators are obtained from Eurostat. The research methods of fixed effects and Tobit approach are used to study the statistical relevance of the two models. The pairwise causality of variables is tested by Dumitrescu–Hurlin causality test. One result of the study is that technology development, by a decreasing life of products, leads to an increase of waste generation. Therefore, environmentally friendly technologies should be produced.